Development of Capsular Fibrosis Beneath the Liver Surface in Humans and Mice. Issue 1 (27th August 2019) - Balog, Steven; Li, Yuchang; Ogawa, Tomohiro; Miki, Toshio; Saito, Takeshi; French, Samuel W.; Asahina, Kinji
Abstract : Glisson's capsule is the connective tissue present in the portal triad as well as beneath the liver surface. Little is known about how Glisson's capsule changes its structure in capsular fibrosis (CF), which is characterized by fibrogenesis beneath the liver surface. In this study, we found that the human liver surface exhibits multilayered capsular fibroblasts and that the bile duct is present beneath the mesothelium, whereas capsular fibroblasts are scarce and no bile ducts are present beneath the mouse liver surface. Patients with cirrhosis caused by alcohol abuse or hepatitis C virus infection show development of massive CF. To examine the effect of alcohol on CF in mice, we first injected chlorhexidine gluconate (CG) intraperitoneally and then fed alcohol for 1 month. The CG injection induces CF consisting of myofibroblasts beneath the mesothelium. One month after CG injection, the fibrotic area returns to the normal structure. In contrast, additional alcohol feeding sustains the presence of myofibroblasts in CF. Cell lineage tracing revealed that mesothelial cells give rise to myofibroblasts in CF, but these myofibroblasts disappear 1 month after recovery with or without alcohol feeding. Capsular fibroblasts isolated from the mouse liver spontaneously differentiated into myofibroblasts and their differentiation was induced by transforming growth factor beta 1 (TGF‐β1) or acetaldehyde in culture. In alcohol‐fed mice, infiltrating CD11b + Ly‐6C Low/– monocytes had reduced mRNA expression of matrix metalloproteinase 13 and matrix metalloproteinase 9 and increased expression of tissue inhibitor of matrix metalloproteinase 1, Tgfb1, and interleukin‐10 during resolution of CF. Conclusion: The present study revealed that the structure of Glisson's capsule is different between human and mouse livers and that alcohol impairs the resolution of CF by changing the phenotype of Ly‐6C Low/– monocytes.